Preformed donor‐specific HLA antibodies are associated with increased risk of early mortality after liver transplantation. Issue 12 (20th October 2016) - McCaughan, Jennifer A.; Robertson, Victoria; Falconer, Stuart J.; Cryer, Claire; Turner, David M.; Oniscu, Gabriel C.
Abstract: There is limited evidence for a negative impact of preformed, donor‐specific HLA antibodies (DSA) identified by cross‐matching on outcomes after liver transplantation. Three recent studies have suggested an association between preformed DSA detected by Luminex and reduced graft or recipient survival in liver transplant cohorts with a high prevalence of hepatitis C. This study investigated the impact of preformed DSA identified by Luminex in the Scottish liver transplant population. All recipients of liver transplants in Scotland between 2007 and 2015 with samples available for day of transplant antibody testing and donor HLA typing were included (n=459); 96% of the cohort were white and 19% had a primary diagnosis of hepatitis C. The median follow‐up time was 36 months. Preformed DSA were detected in 88 recipients. In multivariate analysis, preformed DSA with a median fluorescent intensity ≥10 000 were associated with recipient mortality at 1 year. There was no association between DSA and overall graft or recipient survival. This study adds to the growing body of evidence supporting a detrimental impact of preformed, high‐level DSA in a subset of liver transplant recipients by identifying an association in an ethnically and demographically distinct liver transplant population.